Cabin porn - Klein, Zach, 1982-; Leckart, Steven; Kalina, Noah; Beaver Brook (N.Y. : Commune) (New York, New York : Little, Brown and Company, 2015)
"Rural escapes for those yearning for a simpler existence, by the creators of the wildly popular Tumblr Cabin Porn. Created by a group of friends who preserve 55 acres of hidden forest in Upstate New York-Cabin Porn began as a scrapbook to collect inspiration for their building projects. As the collection grew, the site attracted a following, which is now a huge and obsessive audience. The site features photos of the most remarkable handmade homes in the backcountry of America and all over the world. It has had over 10 million unique visitors, with 350,000 followers on Tumblr. Now Zach Klein, the creator of the site (and a co-founder of Vimeo) goes further into the most alluring images from the site and new getaways, including more interior photography and how-to advice for setting up a quiet place somewhere. With their idyllic settings, unique architecture and cozy interiors, the Cabin Porn photographs, are an invitation to slow down, take a deep breath, and feel the beauty and serenity that nature and simple construction can create"--
Introduction : Beaver Brook: how to build a community -- Backcountry: how to make a homestead in the wilderness -- Fixer-uppers: how to revive a bungalow -- Rustic: how to craft an off-grid bunkhouse -- Purpose-built: how to make maple syrup -- Treehouses: how to live 30 feet in the air -- Modern: how to build a simple shelter -- Earthen: how to live underground -- Salvaged: how to convert a grain silo -- Geometric: How to build a yurt.
Keywords: Log cabins -- United States; Vacation homes -- United States; Cottages -- United States; Small houses -- United States; Tree houses -- United States; Cottages; Log cabins; Small houses; Tree houses; Vacation homes; United States